Correlating Emotional Intelligence With Job Satisfaction: Evidence From a Cross-Sectional Study Among Secondary School Heads in Khyber Pakhtunkhwa, Pakistan - Suleman, Qaiser; Syed, Makhdoom Ali; Mahmood, Ziarab; Hussain, Ishtiaq (Frontiers in Psychology, 2020)
Emotional intelligence is extremely indispensable in functioning leadership positions as leaders wish everybody to fulfill their responsibilities and obligations effectively while job satisfaction has a direct association with the productivity and efficiency of an organization and also to individuals’ success. Therefore, this cross-sectional study examined the relationship between emotional intelligence and job satisfaction among secondary-schools-heads in Khyber Pakhtunkhwa. For this investigation, a total of 402 out of 884 secondary-school-heads were taken as a sample using a multistage sampling technique. The study was correlative, descriptive and quantitative in nature and survey research designed was used for collecting information from the participants. Statistical tools i.e., mean, standard deviation, Pearson’s product-moment correlation, multiple linear regression, and analysis of variance were applied. The findings showed that there was a moderate positive correlation between emotional intelligence and job satisfaction. Additionally, there was a moderate positive correlation between all the subdimensions of emotional intelligence and job satisfaction except emotional stability, where the correlation was also positive and the effect size weak. Furthermore, five dimensions of emotional intelligence such as managing relations, emotional stability, self-development, integrity, and altruistic behavior were found significant predictors of job satisfaction. Therefore, it is imperative to concentrate on those practices that promote emotional intelligence among secondary-school-heads.